Morphological and functional spleen development in crossbreed rabbits - Myroshnychenko, I. I.; Lieshchova, M. A. (Regulatory Mechanisms in Biosystems, 2024)
The accelerated growth of muscle mass in productive broiler breeds is often associated with delayed organ development of integral body systems, particularly the immune structures. The spleen is the largest secondary immune organ in the mammalian body and is responsible for initiating immune responses to blood-borne antigens. It can only perform this function successfully if all of its tissue components are fully morphologically and functionally mature. The spleen was studied in meat production rabbits (early maturing crossbreed Hyplus) at 1, 10, 20, 30, 60 and 90 days of age. Morphological studies included anatomical dissection, clarification of topography, determination of mass parameters, preparation of smears and histological sections. Spleen histological sections were stained with haematoxylin and eosin, according to Van Gieson, and impregnated with silver nitrate, followed by microscopy. Qualitative and quantitative indicators of spleen cellular and tissue component development were determined using ImageJ software. It was found that in crossbred rabbits the topography of the spleen corresponds to general anatomical principles of localisation, has a fixed place and is an anatomically formed organ. In day-old animals, the histological differentiation of the spleen is limited to the connective tissue stroma and the parenchyma. The organ’s parenchyma is formed by reticular tissue, with hematopoietic and lymphoid cells among the cells, without differentiation into white and red pulp. In 10-day-old rabbits, the white pulp is represented by the periarterial lymphatic sheath (PALS) and marginal zones. Single primary lymphoid nodules without germinal centres are seen in the spleen from 20 days of age. By 30 days of age, the white splenic pulp has all the major structural and functional zones, including formed lymphoid nodules with germinal centres and mantle zones. During the second and third months of life, the spleen gradually increases the relative area of all white pulp functional zones, reaching a maximum at 90 days of age. In productive rabbits, the cellular composition of the splenic white pulp is represented by lymphocytes (small, medium, large), reticular cells, macrophages and plasma cells. During postnatal ontogenesis, the number of small lymphocytes increases in all white pulp functional zones, reaching maximum values in 90-day-old animals. On the contrary, the relative number of medium and large lymphocytes decreases. The number of reticulocytes in the periarterial lymphatic sheath and lymphoid nodules zones does not change significantly, and in the marginal zone it decreases substantially by the end of the study. The results of determining the timing of morphological and functional maturation of immunocompetent structures in the spleen of meat rabbits are of great biomedical and economic importance. They will serve as a control for comparing changes in rabbit spleen lymphoid tissues during the development of pathological processes, as well as under the influence of external factors.